2021
DOI: 10.3390/heritage4040167
|View full text |Cite
|
Sign up to set email alerts
|

Geochemical-Microscopical Characterization of the Deterioration of Stone Surfaces in the Cloister of Santa Maria in Vado (Ferrara, Italy)

Abstract: Santa Maria in Vado is a monument in the rich artistic heritage of the city of Ferrara (north of Italy). In this paper we want to investigate the state of conservation of tombstones, cloister and the entrance to the basilica, in order to keep them in the best possible state for the future generations. From the chemical characterization, the state of conservation was determined focusing on the biodeteriogenic and non-biodeteriogenic factors, which determine a series of unwanted changes in the physical, mechanic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 50 publications
(53 reference statements)
0
0
0
Order By: Relevance
“…The optical stereomicroscope (90× total magnification) equipped with MOTICAM 2500 5.0 M pixel webcam using the Motic Images Plus 2.0 ML software was used for reflected light observation on all the samples to define their structural aspect (grain size and texture), clasts dimensional, and morphological aspect of their state of conservation [35]. In this specific work, OTLPM provided information about the quality of the work to produce the mortar [36,37].…”
Section: Stratigraphic Analysesmentioning
confidence: 99%
See 1 more Smart Citation
“…The optical stereomicroscope (90× total magnification) equipped with MOTICAM 2500 5.0 M pixel webcam using the Motic Images Plus 2.0 ML software was used for reflected light observation on all the samples to define their structural aspect (grain size and texture), clasts dimensional, and morphological aspect of their state of conservation [35]. In this specific work, OTLPM provided information about the quality of the work to produce the mortar [36,37].…”
Section: Stratigraphic Analysesmentioning
confidence: 99%
“…The iso-distribution of conductivity highlighted an anomalous area in correspondence with the gap in the plaster (colored in red in Figure 5 to be compared with Figure 4), which indicated that the finishing layers created a barrier to humidity (colored in green in Figure 5). 2500 5.0 M pixel webcam using the Motic Images Plus 2.0 ML software was used fo flected light observation on all the samples to define their structural aspect (grain size texture), clasts dimensional, and morphological aspect of their state of conservation In this specific work, OTLPM provided information about the quality of the work to duce the mortar [36,37].…”
Section: Surface Conductivitymentioning
confidence: 99%
“…2 abundant in the last 30 year focused on the characterization of materials and deterioration processes regarding the lithology, decay mechanisms, causes and restoration procedures [7,8,9,10,11,12].…”
Section: Introductionmentioning
confidence: 99%